INNOVATION AND INVESTMENT PROCESSES IN AGRICULTURAL PRODUCTION AS A FACTOR TO IMPROVE FOOD SECURITY IN RUSSIA - L. P. Goncharenko; T. M. Geraschenkova (Финансы: теория и практика, 2017)
The distinguishing feature of the current situation in the Russian agro-industrial complex is the troubling fact that domestic food production is insufficient while all needed resources are available. In this connection such issues as analysis of specific trends and prospects of food security as well as development and improvement of innovation and investment processes in the Russian agricultural sector are becoming especially relevant. These issues are addressed in this article with reference to the study carried out by the authors in 2012-2013. They used such sources as fundamental and applied research works by Russian and foreign specialists in the field of food security and recent publications on innovation and investment activities in the agro-industrial sector. The calculations were performed on the base of data from the Russian Statistical Yearbook. The work builds on systemic analysis methods. The study highlights the urgency of research on food security within the context of stepping up innovation and investment efforts in the agro-industrial complex. It reports data on the state of agricultural science, the dynamics of investment in research and development in this area as well as investigates into the status of material and technical base of agro-industrial complex and the level of investments in its renovation. The authors reveal some existing barriers to effective investment and innovation. They suggest mechanisms for creating conditions to attract investments in the innovation-oriented development of the sector and show that this is an efficient way to increase food self-sufficiency in Russia. The outcomes of the study can be useful for Russian authorities engaged in economic development of the agricultural sector and for analysts devising food security strategies under the conditions of a globalized world economy.